Care-educational technologies used in primary health care in women's health care: scope review - Rafaela Amaro Januário; Ana Clara de Sousa Cavalcanti; Layane Ruth Jeremias Almeida; Alessandra Emilly Pinto de Assis; Cicera Renata Diniz Vieira; Maria Berenice Gomes Nascimento (Revista de Enfermagem da UFPI)
Objective: To map and identify the care and educational technologies used in Primary Health Care (PHC) in women's health care. Methods: A scoping review was carried out based on the Joanna Briggs Institute manual and guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) Extension for Scoping Reviews. A three-stage comprehensive systematic search was conducted from February to April 2023 in multidisciplinary health sciences databases and gray literature. Data extraction and eligibility were carried out by two authors independently and interpreted using thematic analysis. Results: included 15 studies and identified two thematic groups: Types of care-educational technologies and Themes addressed in the technologies. Conclusion: highlighted the types of care-educational technologies that are used in PHC as fundamental tools for teaching and assisting women's health, making them protagonists in the construction of the health-disease process.